Polypedilum parthenogeneticum (Diptera: Chironomidae): A new parthenogenetic species from Eryngium L. (Apiaceae) phytotelmata - Donato, Mariano Humberto (2008)
All life stages of Polypedilum parthenogeneticum sp. n. are described and figured. The larva lives in the water held in the leaf axils of Eryngium pandanifolium Chamb and Schlecht (Apiaceae). The species is considered to be parthenogenetic as only females were obtained by rearing in the laboratory. Preliminary notes on the biology of P. parthenogeneticum are given.